Ranibizumab inhibits human tenon’s fibroblast proliferation via p21 dependent p53 mechanisms - Siti Munirah Md Noh; Siti Hamimah Sheikh Abdul Kadir; Sushil Vasudevan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Trabeculectomy is the gold standard procedure performed in glaucoma when topical medication and laser intervention failed. In a trabeculectomy, number of clinical trials have shown the efficacy of ranibizumab in minimizing extracellular matrix accumulation at the filtering site. Ranibizumab (LucentisTM) is a drug that targets vascular endothelial growth factor (VEGF). However, to date the actual mechanisms of this anti-VEGF in trabeculectomy is still not well understood. Hence, in here we aimed to elucidate the effects of ranibizumab on human Tenon’s fibroblast (HTF) isolated from patients undergoing trabeculectomy. In our previous study, we had reported that ranibizumab reduces the level of spermidine metabolite whereby spermidine is an important polyamine for cell proliferation. For this current study, cultured HTFs were divided into untreated, control IgG, ranibizumab only, difluoromethylornithine (DFMO; inhibitor of spermidine) only and ranibizumab with DFMO. All cells were extracted for PCR array (expression of CDKN1A, CDK2, and CDK4) and protein expression of p53, p21, CDK2, and CDK4 by Western Blot. In here, our result demonstrated that cells treated with ranibizumab or DFMO and cells treated with ranibizumab-DFMO have similar effects as both show increased in p53 and p21. Meanwhile, no significant differences in expression of CDKN1A, CDK2 and CDK4 were observed in all groups. In essence, our findings suggest that ranibizumab action is mediated by p21 and p53.